Implementasi Metode Waterfall dalam Merancang Sistem Digitalisasi Ruang Baca - Eka Hartati; Yarza Aprizal (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
The focus of this research is implementing the waterfall method in designing a reading room digitalization system. The system development method uses the waterfall method, which consists of software requirements analysis, design, program code creation, testing, and maintenance, while system modeling uses data flow diagrams. This system is tested using black box testing with the type of Balance Equivalence Partitioning and Sample Testing, which is used to ensure that the selected values can produce good data and match the data entered by the user. The results of this research show that applying the waterfall method to building a reading room digitalization system can be done well because this method is unidirectional, meaning that each phase must be completed before the next phase begins, and the system is built where the requirements have been clearly defined from the start and are not possible to change randomly. significant during development